ChemInform Abstract: Cytotoxic Xanthones from Hypericum chinense. Issue 18 (6th May 2014) - Li, Yinke; Xu, Yong; Wu, Jia; Wang, Sujuan; Meng, Yanlin; Ye, Yanqing; Yang, Haiyin; Gao, Xuemei; Hu, Qiufen
Abstract Two new xanthones are isolated and their structures are elucidated.